(untitled) (Research, Society and Development, 2021)
Objective: In this study, we aim to evaluate whether the presence of malnutrition in children and adolescents with infectious diseases is associated with high nutritional risk obtained by the STRONGkids instrument. Methods: A cross-sectional study comprising 237 hospitalized patients aged between 30 days and 18 years. Identification and diagnosis data, weight and height were collected. STRONGkids determined nutritional risk. Acute malnutrition was classified by BMI/age Z score < - 2 and chronic by Height/age Z score < - 2. Associations between categorical variables were verified using Pearson’s chi-square test. A logistic regression analysis was performed to assess the association between anthropometric parameters of malnutrition and nutritional risk. It was considered significant p< 0,05. Results: In multiple analysis, it was observed that having malnutrition as of BMI/age increases the chance by 5.68 of having high nutritional risk by the STRONGKids instrument, regardless of age, sex and the presence of poverty-related infectious diseases (OR: 5.68; 95% CI: 1.54-20.93; p=0.009). Conclusion: In summary, for patients with infectious diseases, acute malnutrition (BMI/age) is associated directly with the diagnosis of high nutritional risk by STRONGkids.